COMPARATIVE ANALYSIS OF E-ADVERTISEMENTS BETWEEN TIKTOK AND INSTAGRAM AMONG THE MILLENIALS - Juan Joshua Rumopa; James D.D. Massie; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2024)
The dynamic landscape of digital marketing strategies within Manado City's millennial population. The research focuses on TikTok's short-form video dominance and Instagram's visually rich platform, exploring their distinct advertising features like TikTok's creative video ads and Instagram's versatile formats such as stories, carousels, and influencer collaborations. Not only does the research highlight potential challenges like misrepresentation leading to dissatisfaction and impulse buying tendencies in e-advertisements, but it also emphasizes the critical role of information accuracy, brand engagement tactics, and the significant impact of electronic word of mouth (eWOM) on purchasing behavior. By assessing the strengths and weaknesses of both platforms, the study aims to offer comprehensive insights into effective digital marketing practices, aiding businesses in optimizing their advertising strategies for increased brand recognition, engagement, and sales among the vibrant millennial community in Manado City. Keywords: information quality, brand awareness, willingness to purchase, E-WOM, e-advertisement